Digital HR A Critical Management Approach to the Digitilization of Organizations - Manuti, Amelia (Springer International Publishing, 2018)
This book draws on recent debate surrounding the emergence of cognitive intelligence in organizations, exploring the redefinition of the labor market and consequently, employment. With a particular focus on Human Resource Management (HRM), the authors analyse the socio-cultural transformation of traditional practices and methodologies that are ocurring in the workforce. Digital HR presents detailed case studies and interviews with HR managers of large multinational companies, providing comprehensive empirical evidence for academics and students interested in the development of HRM in today's digital landscape. The book will also be valuable to practitioners and managers looking to adapt the role of HR in their own companies or organizations.